From Islamic Modernism to Traditional Islam: The Impact of Conflict on the Shifting of Religious Authority in Aceh - Alkaf, M.; Abdullah, Irwan; Qodir, Zuly; Jubba, Hasse (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2022)
This article discusses the impact of conflict on the shifting of religious authority in Aceh. It aims to complement the limitation of current studies, which emphasize conflict as a struggle for natural resources, a means for regional identity, and an effort to develop central-regional power relations. However, the conflict also generates the shift of religious authority, in particular, from modernist Islam to traditional Islam. Data were collected from literature and other related secondary sources. This study found that religious contestations, between the modernist and the traditional Islam groups, have begun in the early 20th century. It used to be a space for religious discourse; hence, it turned into a protracted social and armed conflict. It began with a social revolution, which led the modernist scholars in charge. Nevertheless, the involvement of the modernist ulama in the Darul Islam rebellion affected their influence. The shift in authority began to emerge by the raising of the Free Aceh Movement (GAM) rebellion. During post-Darul Islam, traditional ulama occupied rural communities, and they confronted the GAM in society, as they were involved in bureaucracy. The modernist Islam groups strengthen their position in bureaucracy or seek input from other modernist Islam groups.